ANALISA PEMBENTUKAN FILMWISE MENJADI DROPWISE PADA PENANGKAP UAP JENIS DATAR, SEGITIGA DAN SETENGAH LINGKARAN - Irfan Santosa; Septian Ade Maulana (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
This study aims to determine the formation of filmwise to dropwise, calculate heating heat, calculate the mass of evaporation, calculate the heat transfer coefficient of condensation and the Reynold value. The research method is by varying the shape of the steam catcher and measuring the water temperature (T1), steam temperature in the water heater (T2), steam catcher plate temperature (T3), environmental temperature (T4), taking documentation to see the process of forming filmwise to dropwise. The results showed that heating water required 284,705.42 Joules. Evaporation mass 0.13 kg. The condensation heat transfer coefficient for each of the vapor traps is hdatar = 1.2759 W / m2 0K, triangle h = 1.0493 W / m2 0K, h half circle = 1.1095 W / m2 0K. The Reynolds number is the Re value of the flat steam catcher = 4547487.192, the Re value of the triangular steam catcher = 4088577.645, the Re value of the semi-circular steam catcher = 4323144.511. which means that the steam flow is included in the Turbulent flow.